2021
DOI: 10.12933/therya-21-915
|View full text |Cite
|
Sign up to set email alerts
|

Visitation patterns of jaguars Panthera onca (Carnivora: Felidae) to isolated water ponds in a tropical forest landscape

Abstract: Jaguar populations have declined dramatically in the last century.  The Maya Biosphere Reserve (MBR) within the Selva Maya (SM) is a priority area for jaguar conservation.  Influential factors in the jaguar seasonal distribution include the availability of surface water in wetlands such as the “aguadas” and the availability of prey.  Aguadas are formed by isolated depressions in the landscape and serve as a water supply for wildlife during dry periods.  The goal of this study was to describe the visitation pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…We did not find that habitat use of jaguars was positively related to water sources as previously found (Foster et al., 2010). This could be partly attributed to limitations of our water source layer, which lacked information on streams, intermittent rivers, wetlands, ponds, marshes, and rainwater ponds ‘aguadas’ ‐the latter important for jaguars in dry areas away from permanent/large water sources (Gaitán et al., 2020). Nonetheless, previous research has shown that jaguars with home‐ranges distant from watercourses exhibit responses independent from water locations (Morato et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We did not find that habitat use of jaguars was positively related to water sources as previously found (Foster et al., 2010). This could be partly attributed to limitations of our water source layer, which lacked information on streams, intermittent rivers, wetlands, ponds, marshes, and rainwater ponds ‘aguadas’ ‐the latter important for jaguars in dry areas away from permanent/large water sources (Gaitán et al., 2020). Nonetheless, previous research has shown that jaguars with home‐ranges distant from watercourses exhibit responses independent from water locations (Morato et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although these areas show high ecological integrity, there is low availability of superficial freshwater during the dry season, which is only available in isolated intermittent water ponds, locally known as ''aguadas''. As main freshwater sources during the dry season, ''aguadas'' are relevant landscape features that influence the temporal and spatial use of jaguars and prey species (Gaitán et al, 2021;Sánchez-Pinzón et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Resident jaguars have been identified with the use of camera-traps data on the basis of distinctive coat patterns of each individual providing data on life history parameters (Gaitán et al, 2021;García-Anleu et al, 2015;Harmsen et al, 2009Harmsen et al, , 2017Olson, Matzinger et al, 2019;. Some of these studies had highlighted the importance of border areas for the conservation of this species through the movements of individuals between populations in different countries (García-Anleu et al, 2020;McCain & Childs, 2008;Mena et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Tikal National Park and Maya Biosphere Reserve comprise low-land at elevations of 307-630 m with karstic and permeable soils, whereas the lower areas of the forest have the highest percentage of clayey soil and less permeability. These conditions favour the formation of water ponds that store rainwater during rainy season and become main bodies of water during dry season, playing an ecological importance for interaction of individual Jaguars (García et al 2018;Gaitán et al 2021).…”
Section: Study Areamentioning
confidence: 99%